A Review: Photodynamic Therapy on Wound Healing - Hasnita Hasnita; Hariyanti Hariyanti; Asmiyenti Djaliasrin Djalil (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
Background: Wound infection poses a significant challenge in wound healing, so overcoming microbial infections and accelerating wounds can be done using PDT (Photodynamic Therapy).Â PDT is a non-invasive therapeutic method, light-based therapeutic method that can treat several pathological conditions such as wound healing, antimicrobial, antibiotic resistance bacteria, cancer, and skin repair. Objective: The review article aims to evaluate the effectiveness of PDT in accelerating wound healing. Methods: All articles in this review were taken from the Pubmed and Google Scholar internet databases from 2019 to 2024. Results: Twelve photosensitizers were explored for wound healing using PDT. Some were used in singular form, while others were used in combination. PDT promotes wound healing by killing bacterial cells and stimulating fibroblast proliferation, producing collagen and elastin. The mechanism for faster wound healing was detected by increasing the epithelialization process, decreasing angiogenesis, reducing the number of fibroblast cells, and raising collagen density. Conclusion: Based on research, PDT uses a specific photosensitizer that is activated by light to produce Reactive Oxygen Species (ROS) so that in wound healing, PDT stimulates the wound healing process by improving the quality of tissue formed, fast wound closure, reducing the risk of complications, increasing blood circulation, reduces inflammation and promotes the proliferation of cells involved in tissue regeneration.